Vigilante dawn : a Ralph Compton novel - Compton, Ralph (Signet, 2014)
"When young Jarret Pekoe aims to bring a band of violent border-jumpers to justice, his sister hires rifleman Lem Beauchamp to scare some sense into him. But when trouble arrives, they must work together to defeat the outlaws once and for all" --